Teun A. Van Dijk Discourse Analysis of Social Issues in the song “know Your Enemy” and “21Guns” by Green Day - Natalino Alvares Talalab; Suhartawan Budianto (PT. Padang Tekno Corp, 2025)
Social issues are often represented and maintained through discourse, reflecting and reinforcing the existing power structures and inequalities in society. The thesis writer use method Qualitative design, qualitative research allows for in-depth exploration of phenomena in natural settings, providing rich and detailed insights into the subject matter. In collecting data in the study using 4 stages, among others, selection of song, collection of lyrics, review of lyrics, contextual information. the research results obtained are in the Lyrics songs